The Impact of the EFQM Model on Business Sustainability using Structural Equation Modelling - Maulana, Danis; Beauty, Nur Lailany Fenny; Rachman, Farizi; Hardiyanti, Fitri; Arif, Muhammad Lukman (Jurnal Entrepreneur dan Entrepreneurship, 2024)
Wirausaha Merdeka is a program initiated by the Republic of Indonesia's Ministry of Education, Culture, Research, and Technology. This study is aimed at students who have an interest in the world of entrepreneurship. Shipbuilding Institute of Polytechnic Surabaya adopts the Project Based Learning Technopreneurship learning scheme. Through this program, 103 new businesses have been created in various fields of business. As new businesses, they are susceptible to failure due to several factors. The method of this study used a survey that has been conducted, there are 77.7% of tenants who do not continue their business after the program. This indicates a high rate of business failure among entrepreneurs. This research is conducted to identify the factors influencing business sustainability using the Structural Equation Modelling method. The variables used in this study are derived from the European Foundation for Quality Management Model 2020. The results of this study is that organizational culture and leadership, driving performance and transformation, as well as strategic and operational performance positively influence business sustainability. Purpose, vision and strategy, creating sustainable value, and stakeholder perception negatively influence business sustainability. Meanwhile, engaging stakeholders does not significantly affect business sustainability.